Mode degeneracy and enhanced sensitivity in electrically injected PT-symmetric semiconductor laser with a quasi-high-order exceptional point. (23rd November 2021) - Chen, Jingxuan; Wang, Yufei; Fu, Ting; Wang, Xueyou; Dai, Yingqiu; Zheng, Wanhua
Abstract: Exceptional points (EPs) can be exploited for a new generation of sensors. We propose an electrically injected parity-time (PT)-symmetric three-ridge semiconductor laser. By introducing the non-zero next-nearest-neighboring coupling coefficient to the Hamiltonian obtained by coupled mode theory, the results of eigenspectra match well with those of numerical simulation obtained by finite element method. Based on the introduced coupling coefficient, we develop our design and obtain a quasi-third-order EP. We analyze the eigenmode splitting vs perturbation strength at the EP, which proves that our design is rather sensitive to the external perturbation and possesses the potential to be applied as active high-sensitive sensors.